Dysleksja u dorosłych a depresja – w perspektywie narracji uczestnika terapii pedagogicznej - Wejner-Jaworska, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
This article presents the problem of adult dyslexia and its emotional-motivational effects – the depressive disorders. It shows the narration of a young man experiencing both. From the presented quotations emerges the image of these disorders, but also ways to deal with them. In spite of serious problems, a high level of aspirations has been maintained, and psycho-pedagogical therapy remains a supportive factor as well as success.